Effects of Orofacial Muscles Exercise Program on Swallowing Function and Satisfaction in Sub-Acute Stroke Patients with Dysphagia (Medico Legal Update, 2019)
Background/Objectives: The aim of present study was to examine the effect of orofacial muscle exercise programs on swallowing function with smartphone video as well as satisfaction with outcome in sub-acute stroke patients with dysphagia.Method/Statistical Analysis: We enrolledsub-acute phase of sixteen stroke patients with dysphagia. The participants were randomly assigned to the study group (orofacial muscle exercise program using smartphone video) orcontrol (paper-based orofacial muscles exercise program). All subjects completed their prescribed orofacial muscle exercise programs 20 min/day, 3 times per week, for 4 weeks. The outcome measures were the FDS(Functional Dysphagia Scale), PAS (Penetration-Aspiration Scale) and VASS(Visual Analog Satisfaction Scale).Main analysis was Mann-Whitney U test for comparison between groups.Findings: After intervention, there were no significant differences in swallowing function between the two groups. Nevertheless, in study group satisfactionwas significantly higher than that of the control group.Improvements/Applications: Authors suggest that orofacial muscle exercise programs using smartphone can have a more positive impact on satisfaction than can paper-based orofacial muscle exercise programs in sub-acute stroke patients with dysphagia.